Badania nad rodziną w poznańskim środowisku naukowym - Wierzchosławski, Stanisław (Wydział Prawa i Administracji UAM, 1985)
Family is a difficult and complex subject of the scientific research. It is effected by a number of reasons which are making matters difficult in the degree and range not encountered in other domains of social studies. Although the interest payed to the family by the social sciences in Poland has already a rich and long standing tradition, particular scientific disciplines have been including themselves to the studies in various periods of time. Relatively the earlies participation has been noted in anthropology and ethnography, next in sociology, demography, social psychology, economic sciences, law and recently, in ecology and medical sciences. Various scientific centeres in the country are engaged in the studies. As the research proceeds, the Poznań center is taking the leading position transforming itself gradually in the main center of studies on population microstructures in Poland. Two centrally directed problems are being coordinated in that center: of sociological research (University of Poznań) and of demographic research (Academy of Economics in Poznań). Within the structure of the latter, there is the sole Polish Bank of Information on Family and Household functioning, gathering wide resources of materials handled in three informatic systems: of past, present and future family. Upon reviewing the main trends of studies, the author attempted at estimating the present stage of studies on family in Poland. In the development of empi - rical studies our country has advanced to the head of European states, but the methodological studies, in spite of certain achievements, reveal still considerable retardation in relation to the general level of science in that field. There are substantial disproportions observed between particular scientific disciplines in the scope of improving their research devices and in the effect they are not equally participating in studies on family. Multldisciplinarity of research on family introduces several serious implications which are calling for urgent solutions. In the present stage of research developement the efforts should be directed into: 1) elaboration of principles of the most effective cooperation of numerous scientific disciplines, 2) searching for institutional solutions airned at securing the uniform material and methodological coordination of the whole studies, 3) devicing principles of the inderdisciplinary scientific synthesis for the research results, which would answer the modern stage of sciences development and the social needs.
Studies on family in the scientific circles of Poznań